The Effect of Weight Ratio on the Physiochemical Properties of Compost From Palm Oil Mill Effluent (POME) Sludge and Decanter Cake - N. H., Ramli; N. E., Badrul Hisham; Farhan, Mohd Said; T., Mariyappan (AENSI Publishing, 2016)
POME sludge and decanter cake can be utilized as compost fertilizer since it contains various nutrients which is essential for the plant to grow. In this work, POME sludge and decanter cake were mixed at different weight ratio in the range of 2:8 to 8:2 and undergo composting process for 60 days. Throughout the composting process, temperature is monitored to ensure that the sample has completed the process. After composting process completed, the matured compost is analyzed for chemical composition, pH, moisture content and water holding capacity. The temperature profile of composting shows a stable response between the time composted and the composting temperature. Meanwhile, the physical and chemical properties for sample with ratio of 5:5 (POME sludge: decanter cake) exhibit the best N, P, K ratio of 3:6:11 and other macronutrient and micronutrient compared to samples with ratio of 8:2 and 2:8.